PENGARUH MODEL PEMBELAJARAN GENERATIF TERHADAP PEMAHAMAN KONSEP SISWA KELAS VIII MTs N DI KABUPATEN PESISIR SELATAN - Yanti Nazmai Ekaputri (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2016)
This research was conducted due to the students’ conceptual understanding in class VIII of MTsN in Kabupaten Pesisir Selatan was still low. This problem could be seen from the result of observation done to the students and interview done to mathematics teachers in MTsN in Kabupaten Pesisir Selatan. To overcome the problem, generative learning model was applied. The purpose of this research was to reveal the effect of using generative learning model on the students’ conceptual understanding. This was a quasi experimental research. The data collected was analyzed by using t’ test and Mann Whitney U test. Based on the result of data analysis, it was figured out that conceptual understanding of the students taught by using generative learning model was better than that of students taught by using conventional learning.